“The Scream”: Using the Visual Critical Pedagogy of Subversive Indigenous Art in the Elementary Classroom to Discomfort the Comforted and Activate the Empathic, Ethical, and Relational Dimensions of Reconciliation - Brar, Victor (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2023)
This paper uncovers my journey as K-12 practitioner in British Columbia towards exploring the use of “subversive art” as a “visual critical pedagogy” (Gil-Glazier,2015; Naidus,2005; Peters, 2016; Zorilla & Tisdell, 2016) to advance my students and myself towards reconciliation with Indigenous Peoples in Canada. I use the powerfully unsettling painting done by Cree artist, Kent Monkman, titled “The Scream”, as a springboard for this inquiry. “The Scream” provides an Indigenous counternarrative to the colonial versions of residential school histories and has the potential to progress practitioners and students towards actionable reconciliation by activating their empathic and ethical consciousness. I attempt in this essay to weave together a cluster of concepts, as I explore: (a) the nature and evolution of truth in BC’s elementary school curriculum (Andersen, 2017); (b) the historical establishment of the curriculum in a positivist modality (Gadamer, 2013; Greene, 1975; Marker 2004); (c) Greene’s (1995) argument that aesthetic education can help students and practitioners to engage meaningfully with difficult knowledge; (d) Greene’s (1977, 1995) philosophy of wide-awakeness, through which students and practitioners can activate the power of difficult knowledge; (e) Gadamer’s (2013) “fusion of horizons” as a means by which wide-awakeness can function in this context; (f) “subversive art” as a form of “visual critical pedagogy” (Gil-Glazer, 2015); (g) and the critical pedagogy of Paulo Freire. I braid these concepts together using the scholarship of Indigenous scholar, Michael Marker (1951-2021) to provide the pedagogical rationale for my determination to establish the visual critical pedagogy of “subversive art” in my classroom.